Acute Streptococcus mitis Sacroiliitis in a Teenager with Unclear Source of Bacteremia: A Case Report and Literature Review - Fatma Al-Farsi; Ibrahim Al-Busaidi; Khalfan Al-Zeedi (Case Reports in Infectious Diseases)
Septic arthritis is an orthopedic emergency that is commonly caused by Staphylococcus aureus. Old age, diabetes mellitus, rheumatoid arthritis, prosthetic joint, and recent surgery are the main predisposing risk factors. Most cases of septic arthritis are caused by hematogenous spread of infection. Infectious sacroiliitis is a rare form of septic arthritis which is often clinically challenging to diagnose due its various and nonspecific presentations. Streptococcus mitis belongs to viridans group streptococci (VGS) bacteria, which is a component of body flora that is commonly involved in bacterial endocarditis. VGS in general and S. mitis specifically is an uncommon cause of osteoarticular infections. Here, we report a case of spontaneous Streptococcus mitis bacteremia complicated by septic sacroiliitis in a healthy teenager in the absence of infective endocarditis or a clear source of bacteremia.